Anacoracid sharks and calcareous nannofossil stratigraphy of the mid-Cretaceous ‘upper’ Gearle Siltstone and Haycock Marl in the lower Murchison River area, Western Australia - Siversson, Mikael; Cook, T.; Ryan, H.; Watkins, D.; Tatarnic, N.; Downes, P.; Newbrey, M. (Taylor & Francis, 2018)
Extensive bulk sampling over the past 20 years and greatly improved stratigraphic control permitted a meaningful revision of previously described anacoracid sharks from the ‘upper’ Gearle Siltstone and lower Haycock Marl in the lower Murchison River area, Western Australia. Isolated teeth of anacoracids are rare in the lower three (Beds 1–3) of four stratigraphic units of the ‘upper’ Gearle Siltstone but relatively common in the uppermost layer (Bed 4) and in the lower part of the overlying Haycock Marl. On the basis of calcareous nannofossils, Beds 1 and 2 of the ‘upper’ Gearle Siltstone can be placed in the uppermost upper Albian calcareous nannofossil Subzone CC9b whereas Bed 3 can be referred to the lowermost Cenomanian CC9c Subzone. Bed 1 yielded fragments of strongly serrated anacoracid teeth as well as a single, smooth-edged tooth. The samples from Beds 2 and 3 contained a few small fragments of serrated anacoracid teeth. Bed 4 is barren of calcareous nannofossils but the presence of a dentally advanced tooth of the cosmopolitan lamniform genus Cretoxyrhina in combination with the age of the overlying Haycock Marl indicate deposition within the younger half of the Cenomanian. The unit produced teeth of two anacoracids; Squalicorax acutus sp. nov. and S. bazzii sp. nov. The basal, laminated part of the Haycock Marl is placed in the uppermost upper Cenomanian part of CC10b. It yielded Squalicorax mutabilis sp. nov. and S. aff. S. bernardezi. Exceptionally well-preserved teeth of the former species span a 5:1 size ratio range for teeth of comparable jaw position. The teeth reveal strong ontogenetic heterodonty with a large increase in the relative size of the main cusp with age and the transition from a vertical distal heel of the crown in very young juveniles to a sub-horizontal, well demarcated heel in ‘adult’ teeth. An isolated phosphatic lens in the lower part of the Haycock Marl produced calcareous nannofossils indicative of the CC10b SubZone, most likely the lowermost lower Turonian part. It contains teeth of Squalicorax mutabilis sp. nov., S. aff. S. bernardezi, and S. sp. C.